Drought Tolerant Varieties of Common Beans (Phaseolus vulgaris) in Central Afghanistan - Sayed Muhammad Baqer Hussaini (MDPI AG, 2021)
Legume crops have played a significant role in the historical dietary regime of Afghan peoples. Recently, production of common beans has increased on Afghan farms relative to other leguminous crops. However, compared with other pulse crops, common beans are more prone to water stress. To select drought resistant common beans, several varieties were assessed in the field during a sequence of restricted water supplies for two years and the local drought regime was analyzed for a 12-years period. The first experiment in 2018 compared five bean varieties under four irrigation regimes. White and black beans with long maturation periods and climber habits, and motley beans, characterized by moderate maturity and semi-climber structures, were susceptible to drought and did not mature well under restricted irrigation and ambient climate conditions. The other two varieties, red and pied beans, adapted to restricted water supplies and the long dry summers; these two varieties were assessed again in 2019. Statistical analyses and inferences based on the 2019 study suggest that red beans are more adaptable to water deficit treatments compared to pied beans. Therefore, red beans are considered a better option given the frequent mid- to late-summer droughts that occur in this region, together with the generally harsh mountain climate and short growing season of the central Afghanistan highlands. As a second varietal choice, pied beans are reasonably drought tolerant based on our findings.